Performance Analysis For Sprain Ankle Rehabilitation System Using Gyro Sensor - Azizi, Muhammad Azizul Raziq; Jaafar, Anuar; Osman, Khairuddin (Science and Engineering Research Support Society, 2020)
Sprain ankle rehabilitation is an exercise to recover full function without limitations and strength of ankle joint under the therapist exercise. Recently, ankle rehabilitation technique is enhanced using an intelligent system compared to a conventional technique. Patients mainly perform ankle exercise by manual therapy can cause a loose interest for them to continue the activity. The objectives of this study are to propose and develop an ankle rehabilitation system platform that acts as a user-friendly device able to execute an ankle with 3 Degrees of Freedom (DoF). The develop device consists of a microcontroller, servo motor, gyro sensor, Wi-Fi Module and Graphical User Interface. The microcontroller connected via internet connectivity with smartphones to control modes of exercise at different speeds according to the user's circumstances. A gyro sensor is embedded onto the robotic platform in order to measure the limitation position angle of the patient’s. The closer the tilt angle achieved reflects the recovery which near to the normal person. The strength movement of ankle ability given by each participant almost 55% able to achieve the limitation range angle for the lower torque stiffness power supply of the servo motor. For higher torque stiffness power supply, almost 35% of each participant’s able to reach the limitation range of movement. Based on the result obtained, the Ankle Rehabilitation System device manages to help significantly or almost fully improve the time healing of sprain ankle patients with more interesting motorized rehabilitation devices compared to a traditional device.